RANCANG BANGUN SISTEM INFORMASI PEMANTAUAN KONDISI TERNAK HEWAN SAPI PADA DINAS PETERNAKAN KABUPATEN BLITAR BERBASIS WEB - Rido, Alim Rahmat; Jusak, Jusak; Lemantara, Julianto (Jurnal JSIKA, 2014)
The Dinas Peternakan Blitar currently has problems of recording system as well as slow process of creating report. In addition, there is a significant different number between the number of veterinarians and the number of cows, which are 22 veterinarians and 189.378 cows. Consequently, problems arised from the cows, e.g. sickness, cannot be handled properly. Based on the underlined, it is necessary to have an information system which allows farmers / communities to perform online consultation in diagnotion cowâs diseases. This system will also useful in giving for early treatment. More over the system is expected by the farm department to record the activities of a veterinarian and personnel artificial insemination in order to view the report quickly.. Based on the result, the information system of cow monitoring condition web based produces report required by the farm department. In addition this system also proved to be able to identify consultation obtained a value 4.14 (on a scale of 1-5), while the results from questionnaire of recording and reporting application menu obtained a value 4.2 (on scale of 1-5). From the statement above, it can be concluded that the application of cow monitoring condition in accordance with the requirements by user and can be easily used.